Brain Booster Pada Ibu Hamil Terhadap Peningkatan Reflek Neurobehavioural Pada Bayi Baru Lahir Di Rb Amanda Sleman Yogyakarta Tahun 2015 - Lilik Hendrarini; Agus Suwarni (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2016)
In order to ensure continuity of the qualified next generation, then it begins from preconception and conception until pregnancy, birth and life as a child. Building child intelligence and child right to life begin from fetus in the uterus. The development of brain structures and circuits that are the factors of intelligence begins in the fetus and hereafter intelligence is influenced by two interrelated factors, those are hereditary factors and environment. Clinical assessment of children's intelligence factors is assessed since newborns. Simple clinical assessment indicator in assessing the intelligence of the fetus or newborn is assessed from the neurobehavioural reflex. Health and stimulation during pregnancy affects the outcomes quality of newborn. Objective of this study is to identify the influence of Brain Booster against Neurobehavioural reflexes of Newborn in RB Amanda Sleman, Yogyakarta in 2015. The study was a true experiment with Randomized Ccontrolled Trial with post-test with control group single blind. Research subjects for the experimental group were pregnant women with Brain Booster treatment while for the control group were pregnant women with ANC routine without Brain Booster. Total sample was 40 samples with 20 respondents for each group. Random sampling technique was used for study subjects which meet the criteria for inclusion. The data were collected using standard instrument of NNNS (Neonatal Neurobehavioural Network Scale) scores and HNNE (Hammersmith Neonatal Neurologic Examination) scores that had been modified. The data were analyzed using independent sample t-test. There were differences in average scores between the treatment groups given Brain Booster compared to the control group without Brain Booster by 23.7 with significance of 0.000 (p-value of <0.05). The difference in the score of each sub-variables of neurobehavioural reflex showed no significant difference between the treatment group and control group, with overall significance of 0.000 (p-value <0.05); including posture and tone score of 8.750, primitive reflex scores amounted to 7.100, activity reflex scores amounted to 2.600, behavior and orientation pattern score amounted to 3.750 and the general status of neurobehavioural was1,500. Threfore, overall scores of neurobehavioural was higher in the treatment group than the control group. Brain booster can increase newborns' neurobehavioural reflexes. Brain booster can improve some aspects of neurobehavioural reflexes including: posture and tone; primitif reflexes; activity response; patterns of movement; orientation and behavior patterns as well as common neurobehavioural status in newborns.